(NZW × BXSB) F1 male mice: An unusual, severe and fatal mouse model of lupus erythematosus - Almizraq, Ruqayyah J.; Frias Boligan, Kayluz; Loriamini, Melika; McKerlie, Colin; Branch, Donald R. (Frontiers in Immunology, 2022)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune/inflammatory disease. The heterogeneity and complexity of clinical presentation has made it challenging to study or treat this syndrome. The (NZW×BXSB) F1 lupus-prone male mouse model of this disease is potentially useful to study mechanism and treatment modalities, but there is a lack of information about this model's characterization and disease progression. Therefore, the aim was to examine this lupus model's physical/clinical disease presentation and its immunological status. Materials and Methods: Clinical and physical status were observed in 8- and 16-week-old male (± 1 week) and female (NZW/LacJ x BXSB/MpJ) F1 mice (n= 8 per group). Young males (8 ± 1 week) without disease and female mice served as controls. Physical changes, quantitative values of autoantibodies, and blood cell parameters were determined. Necropsy and post-mortem histopathology were also performed. Results: With aging (≥ 12 weeks), significant increases in severe abdominal distension/swelling, inability to walk, paleness of paws and significant weight increase were observed compared to controls (p < 0.05). The necropsy examination and histopathology showed abdominal distension associated with severe edema and multi-organ abnormalities (spleen, lymph nodes and kidney). Significant increases in anti-double-stranded DNA antibody (anti-dsDNA) was seen in old/sick compared to female (p = 0.0002) or young male (p = 0.0036) mice. Old mice developed immune thrombocytopenia compared to female (p = 0.0056) and young male (p = 0.0007) mice. Anti-platelet was detectable in old, sick mice. The mortality rate increased with aging; more than 35% of male mice died during this study between the ages of 13-18 weeks. Conclusion: We found that the (NZW/LacJ x BXSB/MpJ) F1 male mice spontaneously exhibit, over varying lengths of time, extremely severe and fatal clinical disease symptoms. This model may be too severe to be helpful in investigating SLE and testing potential treatment modalities.